2008
DOI: 10.1111/j.1445-2197.2008.04616.x
|View full text |Cite
|
Sign up to set email alerts
|

Cure, Continence and Quality of Life After Treatment for Fistula‐in‐ano

Abstract: Functional impairment and QOL do not necessarily correlate. The development of a validated specific QOL scale for patients with anal fistulas would be important to compare the results of different treatment options. This scale should include social and psychological factors in addition to the physical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…A similar discrepancy between clinical outcomes and patient satisfaction had been found previously after the surgical treatment of fistula-in-ano [5,13]. In a retrospective analysis done by Wong et al, a group of patients surgically treated for fistula-in-ano nominated independent activity, pain, continence, psychological health and leakage as the five most important factors that affected their QOL.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…A similar discrepancy between clinical outcomes and patient satisfaction had been found previously after the surgical treatment of fistula-in-ano [5,13]. In a retrospective analysis done by Wong et al, a group of patients surgically treated for fistula-in-ano nominated independent activity, pain, continence, psychological health and leakage as the five most important factors that affected their QOL.…”
Section: Discussionsupporting
confidence: 59%
“…Despite the continuous improvement in preoperative imaging [2,3], the reported recurrence rates vary from 8 to as high as 40% [4]. Recurrent fistula-in-ano carries a significant morbidity affecting the quality of life (QOL) due to the disease as well as due to repeated operations [5]. Sometimes, even after the ''surgical cure'' of a fistula, long-term complications of surgery such as anal incontinence can affect the QOL with a significant negative impact [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, complex fistulas involve more sphincter muscle and cannot be laid open for fear of faecal incontinence. Many surgical techniques have been described for the treatment of such fistulas, including the use of seton, fibrin glue, collagen plugs, rectal advancement flaps, anocutaneous advancement flaps, fistulotomy with sphincter repair and re-routing the fistula tract [1]. The results have been variable, and no one procedure is superior to the others.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Wong et al found that patients and surgeons often have conflicting views on the relative importance of these outcomes. 5 Patients were more concerned with cure of fistula, while surgeons felt strongly that their patients would be more concerned with continence. In our study, 10 patients who had a failed repair elected to 'live with their fistula' and did not undergo a further definitive procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of Australasian colorectal surgeons revealed that a RMAF was the preferred definitive surgical treatment of complex fistulas. 5 The rates of success of such flaps vary widely in the literature from 29 to 95%. [6][7][8][9][10][11][12][13] Despite being called a 'sphincter-sparing procedure', major and minor incontinence rates are reported.…”
Section: Introductionmentioning
confidence: 99%